Intervenciones de enfermería en los programas nacionales de prevención y control de la tuberculosis en Latinoamérica - Kassandra Yajahira, Delgado Serrano (2020)
Tuberculosis is a global health problem, and stopping it is a challenge for humanity. The objective is to determine the effectiveness of including nursing interventions in national tuberculosis prevention and control programs in Latin America. A documentary review was carried out on regulations, technical reports, clinical practice guidelines, and scientific results. The population was 3259 manuscripts disclosed between 2015 and 2020 in Scopus and Scielo. Based on the criteria, 29 regulations, and seven scientific articles, the methodological quality was determined through the Critical Review Form-Quantitative Studies classification. As a result, the active search for respiratory symptoms, BCG vaccination, health education, advice on athymic adherence, and home visits are standard in the TB prevention and control programs consulted. In conclusion, the insufficient role of individuals, families, and communities limits structured actions' effectiveness to stop tuberculosis